2017
DOI: 10.1515/ijamh-2016-0132
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intervention on cardiovascular disease risk factors in a university population in the United Arab Emirates

Abstract: Objective 1) To assess the incidence of cardiovascular disease (CVD) risk factors in a university population, and 2) to investigate the effects of an 8-week exercise intervention on CVD risk factors. Methods Forty-six students participated in this study. Baseline cardiorespiratory fitness was assessed using maximal oxygen uptake (VO2 max). Total cholesterol, high-density lipoprotein (HDL)-cholesterol and triglycerides were measured. Body mass index (BMI), waist-to-hip circumference ratio (WHR), blood pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…Notably, an 8-week exercise intervention programme in a UAE student population demonstrated a significant reduction in BMI. 31 In addition, other controlled intervention studies in high-risk populations 32 33 demonstrated a significant decrease in the risk of type 2 DM consequent to BMI reduction.…”
Section: Risk Factorsmentioning
confidence: 97%
“…Notably, an 8-week exercise intervention programme in a UAE student population demonstrated a significant reduction in BMI. 31 In addition, other controlled intervention studies in high-risk populations 32 33 demonstrated a significant decrease in the risk of type 2 DM consequent to BMI reduction.…”
Section: Risk Factorsmentioning
confidence: 97%
“…The 16 studies that were ultimately included in the review were all published in English between 2012 and 2021. The interventions differed in their study design in seven CCTs (29)(30)(31)(32)(33)(34)(35), four RCTs (36)(37)(38)(39) and five cohort studies with a single group and pre-post design (40)(41)(42)(43)(44). The interventions were conducted in different countries around the world, including four in the USA (30,40,41,39), four in China (36,33,38,34), two in Korea (32,42) and one each in the United Emirates (29), Indonesia (31), South Africa (43), Iran (37), Jamaica (44) and in Saudi Arabia (35).…”
Section: Resultsmentioning
confidence: 99%
“…Pacholek et al (35) divided the sample into two overweight groups to analyze the change in overweight students based on the two different exercise programs. Dalibalta et al (29), in turn, used the same group allocation to use the overweight group as the intervention group (IG) and the normal weight group as the CG. Lee et al (42) has not described its main inclusion criteria in detail.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors who have studied the effects of physical activity on body composition believe that inclusion and engagement in certain physical exercise programs contribute to a decrease in adipose tissue levels. It also provides a sound basis for the prevention of cardiorespiratory and cardiovascular diseases (Kondo, Kobayashi, & Murakami, 2006;Dalibalta, Mirshafiei, & Davison, 2017). The physical activity of the student population and their health habits in youth can affect their health status in adulthood (Tirodimos, Georgouvia, Savvala, Karanika, & Noukari, 2009).…”
Section: Introductionmentioning
confidence: 99%